Penerapan Metode Learning Start With A Question Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Qomaruddin Qomaruddin; Moh. Maghfur; Hana fuadiah (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2023)
This research analyzes the application of the Learning Start With a Question method in PAI learning at UPT SMP 23 Gresik. It was found that the teacher succeeded in implementing this method well. The steps involve students in creating questions from the reading material provided, followed by discussion in class. The advantage is the direct involvement of all students in more interactive learning. However, the weakness is that students who are lazy about reading tend to repeat their friends' questions and sometimes ask things outside the material. The descriptive qualitative method allowed researchers to explain the actual conditions in the field. Data was obtained through observation, interviews and documentation, then analyzed through data reduction, presentation and verification. The research showed an increase in average student grades and positive individual achievements. Even though there are weaknesses, such as students not participating enough in reading and sometimes asking questions outside the material, overall, this method successfully improves PAI learning outcomes. Thus, it can be concluded that Learning Start With a Question effectively increases students' understanding of Islamic religious education in class VII SMPN 23 Gresik.